Claims-based cardiac monitoring (CM) in patients (Pts) receiving trastuzumab (TZ). Issue 28 (1st October 2022) - Bandini, Lindsey; Denlinger, Crystal S.; Duggan Goldstein, Sarah Ford; Marinkovich, Wendy; Edge, Stephen B.; Carlson, Robert W.
Abstract : 324 Background: TZ in HER2-positive breast cancer (BC) has established improved outcomes in certain Pts. TZ carries a black box warning and a recommendation for CM in all Pts prior to and during treatment (tx) Few studies have evaluated real-world CM compliance during tx. Methods: Retrospective, cross-sectional analysis was conducted to identify CM compliance among BC pts receiving TZ, using a limited data set of administrative claims data consisting of female Pts who were continuously insured over a 24-month period between Jan 1, 2019 and Dec 31, 2020, as provided through a secure portal by Blue Cross Blue Shield Association.[1] . BC diagnosis was confirmed by ICD-9 code, while tx with TZ or biosimilar was confirmed through Healthcare Common Procedure Coding System codes. A care episode spanned 14 months, including 123 days prior to first TZ dose (Index Date) and at least 307 days of follow up. Two cohorts (eligibility for both dx and continually insured status of female commercial Pts, 2018-2019 and 2019-2020) were analyzed across four tx Phases (Pre-Tx Phase [days -123-+ Index Date as day 1], Phase 1 [days 61-123], Phase 2 [days 153-215], Phase 3 [days 245-307]). Phase denominators were calculated independently, only including Pts with ongoing TZ tx for each Phase. [1] Blue Cross Blue Shield Association is an association of independent, locally operated Blue Cross and Blue Shield companies. Results: Pts in each Phase and cohort ranged from 2, 304 (Full Compliance 2019-2020) to 3, 263 (Pre-Tx 2019-2020). Similar results were seen in both cohorts, with highest proportion of Pts receiving CM in Pre-Tx phase. Overall compliance in Pre-Tx Phase and all subsequent Phases was low; nearly two-thirds of Pts missed one or more CM tests. Drop-off in CM testing occurred in each subsequent tx Phase (Table). Conclusions: Continued decline in CM over time suggests lack of awareness for potential late TZ cardiac toxicity. Further research regarding why Pts are not receiving recommended baseline and on-treatment CM is needed. Routine CM during TZ tx may be a quality indicator for practices, payers, and quality improvement programs.Percentage pts receiving CM (pts received/pts eligible). Tx Phase 2018-2019 2019-2020 Pre-Tx 81% (2572/3192) 82% (2675/3263) Phase 1 60% (1915/3192) 61% (1999/3263) Phase 2 55% (1590/2867) 54% (1418/2604) Phase 3 53% (1333/2530) 52% (1210/2326) Full Compliance (across time) 32% (792/2500) 30% (700/2304)